Physical properties of Brachystegia Eurycoma seeds as affected by moisture content - Aviara, Ndubisi A.; Ibrahim, Elizabeth B.; Onuoha, Lovelyn N. (International Journal of Agricultural and Biological Engineering, 2014)
Some physical, frictional and thermal properties of Brachystegia eurycoma seed were studied at different moisture contents in order to explore the possibility of mechanizing the handling and processing techniques. Results showed that the seed could be considered an oval disc in shape. In the moisture range of 2.79% to 27.13% (d.b.), the major, intermediate and minor axial dimensions increased with increase in moisture content from 2.29 mm to 2.45 mm, 1.65 mm to 1.91 mm and 0.34 mm to 0.52 mm, respectively. In the above moisture range, one thousand seed weight, particle density, porosity, roundness, sphericity, surface area and angle of repose increased linearly from 0.901 kg to 1.252 kg, 2270 kg/m3 to 2520 kg/m3, 11.23% to 15.46%, 35% to 47%, 67% to 82%, 7.67 cm2 to 8.48 cm2 and 16.8° to 29.2° respectively, while bulk density decreased from 745.4 kg/m3 to 613.6 kg/m3. Static coefficient of friction on different structural surfaces increased linearly with moisture content and had the highest values on galvanized steel sheet (0.445-0.639), and the lowest values on fiber glass (0.287-0.404). Kinetic coefficient of friction increased linearly with moisture content on different structural surfaces except on galvanized steel sheet where it decreased linearly with increase in moisture content in the above moisture range. It had the highest values on hessian bag material (0.266-0.389), and the lowest values on plywood with wood grains perpendicular to the direction of movement (0.204-0.271). Specific heat ranged from 1474 to 5992.7 J/kgK, and increased with increase in moisture content and temperature. Regression equations were used to express the relationships existing between the seed properties and moisture content.